Arduino Uno Based Real Count Development as a Tool to Help Assessing Physical Exercise Results (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The development of previous tools used by researchers to assess physical exercise results only uses one variable. For example, the assistive tool is only for the variables of push-up, sit-up, speed, agility, or reaction. In its development, researchers have created a tool using four variables, named Real Count. This type of development research is used to produce specific products and test the effectiveness of the product, research design, product needs analysis, initial product drafts, expert validation, improvement of initial product drafts, product effectiveness trials and small-scale trials, first product revisions and field trials, and revision of the final product. The instruments used to collect data were interviews, observations, questionnaires, and documentation. Data analysis techniques use a Likertscale of 1-5. The product effectiveness test is in the